Keberpihakan Kebijakan Pemerintah pada Sektor Usaha Rakyat Perspektif Ekonomi Islam (Studi Kasus Keberlangsungan Pasar Tradisional) - Abdul Wahab (TSAQAFAH, 2016)
The economic sector of small-medium enterprises as known in Indonesia with Micro, Small, and Medium Enterprises (MSMEs), has strategic contribution in Indonesian’s economic development. This sector as known was survived when Indonesian affected by the global crisis of economic at 1998 and 2008 ago. This MSMEs also know as a way for absorption of human capital. Therefore, it is need more of Indonesian Government’s consideration as part of economic development policy of Indonesia. The place for trading between MSMEs’s practitioners was called traditional market which ruled by direct transaction and transparent. Traditional traders have been competed with the growing number of mall around the market. In addition to the rivalry with fellow traders in traditional markets. They have a rational strategy as a way of facing competition with modern market. Actually, the Government must maintain sustainability of traditional market with they public policy. Impelementation public policy should refers to Islamic economic, especially concept of distribution of wealth. The distribution of wealth is one of the most important and most controversial subjects concerning the economic life of people, which have given birth to global revolutions in the world of today, and have affected every sphere of human activity from international politics down to the private life of the individual. Then, this paper raised the issue of: condition traditional traders recently, while growth modern market increase so fast; function and role from public policy for supporting suistanability traditional market; and urgency distribution of wealth as strategy on public policy for sustainability of traditional market.